Segmenting graduates consumers of higher education in tourism: An extension of the ECSI Model - Eurico, Sofia (2014)
This research explores the European Consumer Satisfaction Index model applied to higher education in tourism by accounting for unobserved heterogeneity. In particular, it intends to identify segments of Higher Education Institutions’ consumers based on the structural model estimates of the European Consumer Satisfaction Index, enlarged with the employability construct. A model-based segmentation approach in Partial Least Squares path modelling is used. The European Consumer Satisfaction Index was properly adjusted to the educational framework and has shown its effectiveness when assessing students’ satisfaction regarding the attended Higher Education Institution. Two distinctive, graduates’ segments were identified using a sample of 166 Higher Education Institutions’ consumers. Results confirm the assumption of heterogeneity as the relationships differ across segments and the need for Higher Education Institutions to differently target those segments in such a competitive context. These results may be used strategically by Higher Education Institutions and policy makers as segments of graduates are identified according to their perception of employability and the future influence of this on their satisfaction. Deepening the knowledge on their consumers, Higher Education Institutions will be better prepared to adjust their educational performance to graduates’ best interests and to promote their offer.